The Development of Online Program During Pandemic in Menteng Seventh Day Adventist Church Jakarta - Raden Deddy Kurniawan; Stimson Hutagalung; Rolyana Ferinia; Janes Sinaga (Sekolah Tinggi Teologi Berita Hidup, 2021)
The spiritual impact of pandemic Covid-19 is almost felt by every church in Jakarta. In addition to the closure of place of worship, the quality of service to reach each member who survived the pandemic needs to be maintained. Pastor as spiritual leaders in the congregation ought to be wise and creative in dealing with this phenomenon. This research is the result of development of online service that is being carried out by the author as a Pastor at Menteng Seventh-day Adventist Church in Jakarta in order to maintain the spiritual life of the congregation during the pandemic Covid-19. A quantitative approach by taking into the results of observations on the program that are currently being run is expected to help ministers in the congregation to develop consistency and quality of the program. With the advancement of technology in today’s era, the challenge of developing quality in online service to be a blessing for church members is possible. And the results of this development program are not only helping a Pastor to be able to create spiritual programs for the congregation, but more broadly the church can grow spiritually